Mediations and sociodigital interactions related with self-medication among young university students in Mexico - Farías Ochoa, Alberto (2024)
This paper reports the results of a concluded research investigating the selfmedication practice among university students in México. The study suggests that young university students who practice self-medication reinforce this behaviour through social media among their peers. This exploratory research had a qualitative approach and incorporated etnography and interviews (in-depth and semi-structured) as methods for collecting data for further analysis. During the study, several coincidences were found about the practice of self-medication among university students in Mexico, and other investigations reported the same practice among other university students in Latin America. Medication in young people without physician supervision is increasing every day, and accessibility to pharmaceutical products is very common, especially in developing countries. Furthermore, social networks give university students new channels for acquiring medicines. Self-medication in university students requires special attention from multidisciplinary approaches to study the phenomenon through different dimensions and prevent several risk possibilities among this population.